TEACHERS' PERCEPTIONS ON THE MODEL DEVELOPMENT OF CHARACTER BASED TEACHING MATERIAL FOR SMA/ MA STUDENTS IN SEMARANG - Suwandi Suwandi; Sukma Nur Ardini (Celt: A Journal of Culture, English Language Teaching & Literature, 2015)
This study was conducted with the objectives of finding out whether or not the teaching material entitled "English for Better Character" developed by the researchers through R&D was appropriate seen from the point of view of the teachers' perception. Seven English teachers from 7 Senior High Schools and Madrasah Aliyah in Semarang were taken as samples. Data were collected using questionnaires and analyzed by using Likert scale with the criteria of 5:excellent, 4:good, 3:fair, 2:poor, and bvery poor. The questionnaires contained three main aspects, such as the content appropriacy, the presentation appropriacy, and the technique appropriacy. As a whole, the mean of all aspects was 4,12. It indicates that it belongs to the criteria of very good with the following percentage, content: 32,44%, presentation: 32,18% and language: 35,52%. In conclusion, the teaching material for SMA/MA students developed by the researchers is suitable to be used as a teaching material.